THE STUDY OF LONGITUDE DISPERSION PHENOMENON IN FLOW PROBLEMS THROUGH LAPLACE TRANSFORM TECHNIQUE - Patel, Shailesh S. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The present paper discusses the phenomenon of longitudinal dispersion in the flow of two miscible fluids through porous media. An exact solution of partial differential equation arising in this phenomenon has been obtained by Laplace Transform method. A particular case of the former section by regarding flow velocity and dispersion coefficient as constants, and has been solved by method of Laplace transformation. The phenomenon of longitudinal dispersion is the process by which miscible fluids in laminar flow mix in the direction of flow has been discussed.